The challenge of invasive mosquito vectors in the U.K. during 2016–2018: a summary of the surveillance and control of Aedes albopictus. Issue 4 (30th July 2019) - Vaux, A. G. C.; Dallimore, T.; CULL, B.; Schaffner, F.; Strode, C.; Pflüger, V.; Murchie, A. K.; Rea, I.; Newham, Z.; Mcginley, L.; Catton, M.; Gillingham, E. L.; et al.
Abstract: Mosquito‐borne diseases resulting from the expansion of two key vectors, Aedes aegypti and Aedes albopictus (Diptera: Culicidae), continue to challenge whole regions and continents around the globe. In recent years there have been human cases of disease associated with Chikungunya, dengue and Zika viruses. In Europe, the expansion of Ae. albopictus has resulted in local transmission of Chikungunya and dengue viruses. This paper considers the risk that Ae. aegypti and Ae. albopictus represent for the U.K. and details the results of mosquito surveillance activities. Surveillance was conducted at 34 points of entry, 12 sites serving vehicular traffic and two sites of used tyre importers. The most common native mosquito recorded was Culex pipiens s.l . (Diptera: Culicidae). The invasive mosquito Ae. albopictus was detected on three occasions in southern England (September 2016, July 2017 and July 2018) and subsequent control strategies were conducted. These latest surveillance results demonstrate ongoing incursions of Ae. albopictus into the U.K. via ground vehicular traffic, which can be expected to continue and increase as populations in nearby countries expand, particularly in France, which is the main source of ex‐continental traffic. Abstract : Surveillance for invasive mosquitoes was conducted from April to October during 2016–2018. Each year, Aedes albopictus eggs were found in an ovitrap at one motorway service station in Kent. Eggs were identified using MALDI‐TOF mass spectrometry, DNA sequencing (CO1 and ITS2 regions) and morphological identification using scanning electron microscopy images. Control was conducted by local authorities using source reduction and a silicon‐based mosquito control product.